First bite syndrome following surgical management of primary jugular foramen lesion: Clinical experience and review of the literature - Xinrui Xu; Mengye Ma; Qianru Wu; Xunbei Shi; Feitian Li; Chunfu Dai (Brazilian Journal of Otorhinolaryngology)
Objective: This study presents patients with primary jugular foramen lesions who developed First Bite Syndrome (FBS) after surgery, and reviews the literature on advancements in treating FBS. Methods: A retrospective review of 47 patients with primary jugular foramen lesions who underwent surgery between January 2020 and May 2022 was conducted. Results: FBS were identified in 4 patients (8.5%). All 4 patients underwent Infratemporal Fossa (ITF) dissection, Internal Jugular Vein (IJV) ligation, and Internal Carotid Artery (ICA) dissection. None of the patients had the External Carotid Artery (ECA) ligated. The mean duration of FBS was 16-months (range, 6–25 months) with a mean follow-up time of 22 months (range, 20–26 months). All patients reported tolerable FBS symptoms, with an average pain intensity of 2.8 (range, 2–4). None received medical treatment. Conclusion: Patients with primary jugular foramen lesion who undergo ICA dissection may be at risk for developing FBS. However, symptoms are usually mild, and a conservative, wait-and-see strategy is recommended. All patients undergoing surgery for jugular foramen lesions should be informed about the potential risk of postoperative FBS. Level of evidence: 4.